Nonmotor Symptoms in Nursing Home Residents with Parkinson's Disease: Prevalence and Effect on Quality of Life. Issue 10 (1st October 2013) - Weerkamp, Nico J.; Tissingh, Gerrit; Poels, Petra J.E.; Zuidema, Systse U.; Munneke, Marten; Koopmans, Raymond T.C.M.; Bloem, Bastiaan R.
<x xml:space="preserve">Abstract</x> Objectives To determine the prevalence of nonmotor symptoms (NMS) in nursing home (NH) residents with Parkinson's disease (PD) and to establish the association with quality of life. Design Cross‐sectional. Setting Nursing homes in the southeast of the Netherlands. Participants Nursing home residents with PD and a Mini‐Mental State Examination score of 18 or greater (N = 73; mean age 78.7, disease duration 10 years, mainly Hoehn and Yahr Stages 4 (38%) and 5 (49%)) underwent detailed examination to determine the prevalence of NMS. Measurements Validated instruments for PD‐related NMS were used to examine the NH residents with PD. The overall burden of NMS, and autonomic problems in particular, were measured using the Non‐Motor Symptoms Scale (NMSS). Depression, neuropsychiatric symptoms, sleep problems, cognitive dysfunction, and motor impairments were focused on in further detail using established clinimetric tests. Linear regression analysis was used to examine the relationship between these symptoms and quality of life, which was measured using the Parkinson's Disease Questionnaire (PDQ‐8). Results The NMSS revealed a mean of nearly 13 different NMS per resident. Autonomic problems (constipation, urinary urgency) were particularly prevalent (48–75% of residents). Depressive symptoms were present in 45%. The most prevalent neuropsychiatric symptoms other than depression were irritability and apathy. The most common sleep problems were overall poor nighttime sleep quality, daytime sleepiness, and nocturia. Cognitive problems were highly prevalent, and 77% of the residents met the criteria for PD‐related dementia. High scores were also obtained for motor impairments. Mean PDQ‐8 score was high, indicating poor quality of life. Poor quality of life was most strongly associated with the prevalence and severity of overall NMS burden (coefficient of determination = 0.45). Conclusion Nonmotor symptoms were highly prevalent in NH residents with PD. Quality of life was poor, largely because of NMS. Because many NMS are potentially treatable, diagnosis and treatment of these severely affected individuals deserve more attention.